Sistem Informasi Customer Relationship Management Untuk Pengelolaan Liquified Petroleum Gas Pada Pangkalan Sudarsono - Edo Tio Gunawan; Nurahman Nurahman (SMATIKA JURNAL : STIKI Informatika Jurnal, 2022)
The system implemented at Sudarsono Base means one of the LPG Gas bases located in the city of Sampit. Therefore, create a system to manage LPG gas to simplify the order process and deliver a service and various solutions for its customers. As a result, it is hoped that this information system can be useful for the company and structured in a structured manner, especially for the management of the gas order process. As a result, various service tactics can be used by deciding on a service using one of the concepts of correlation management between customers and Customer Relationship Management (CRM) so that they can produce what will occur in the desired business. LPG Gas Management information system is very important for the base. Where the base is difficult to manage data and process orders. Because data writing is still done manually. That is using handwritten one by one which is very prone to errors in entering sales data in reports and also searching for data errors takes a long time. Therefore, an information system is needed to manage customer data, and process orders. in the development of this web-based application program, using VS Code software, various programming languages such as PHP, javascript, and MySQL database.